2021
DOI: 10.1097/gme.0000000000001844
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hormone therapy on breast density following risk-reducing salpingo-oophorectomy in women with an increased risk for breast and ovarian cancer

Abstract: The effect of hormone therapy on breast density following risk-reducing salpingooophorectomy in women with an increased risk for breast and ovarian cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous risk-reducing surgeries should therefore be taken into account in the contraceptive advice for BRCA1/2 -PV carriers. In other cases, the use of contraceptives might influence breast cancer management strategies; for example, OCP might increase breast density, as was previously described for hormone replacement therapy, although the data are inconsistent ( van Barele et al , 2021 ; Evans, 2002 ; Lundström et al , 2002 ). Higher breast density negatively affects the evaluability of imaging techniques.…”
Section: Discussionmentioning
confidence: 95%
“…Previous risk-reducing surgeries should therefore be taken into account in the contraceptive advice for BRCA1/2 -PV carriers. In other cases, the use of contraceptives might influence breast cancer management strategies; for example, OCP might increase breast density, as was previously described for hormone replacement therapy, although the data are inconsistent ( van Barele et al , 2021 ; Evans, 2002 ; Lundström et al , 2002 ). Higher breast density negatively affects the evaluability of imaging techniques.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, chemoprevention trials have shown that tamoxifen treatment is associated with decreasing breast density [ 33 – 35 ]. Also, surgical removal of both ovaries (bilateral oophorectomy) is associated with decreasing breast density [ 36 , 37 ]. However, there have been very limited studies in which other factors were examined for potential association with longitudinal changes in breast density.…”
Section: Discussionmentioning
confidence: 99%